Sekolah Lurah: R-Urban Development Approach in Indonesia - Yulianto Purwono Prihatmaji (UII, 2018)
This paper will present process and ongoing result of Sekolah Lurah program that towards r-urban development approach in Indonesia. Urban development and planning practice in Indonesia has moved from physical to procedural development. This opens the opportunities for greater role for ‘non-government’ stakeholders. It encourages planning procedures to follow a bottom-up approach; but, it is rather a formal approach with insufficient guidance for implementation strategies. Indonesia experiences high levels of urbanization and its associated challenges, particularly in small-medium size cities, which alongside its development strategies have contributed to environmental and natural resource management conflicts. In response, R-Urban approaches advocate alternative ecological model of living, production and consumption between urban and rural. This coincides with the Law No. 6 2014, which focuses on development at R-Urban neighborhood level. The Sekolah Lurah explores the perspective of a comprehensive sustainable development strategy (planning documentation to implementation) in the context of an R-Urban environment. Purposive activities carried out in several area that has specific excellences for tourism, agriculture, craftsmanship and culinary.